Efficacy of combined approaches of periocular reconstruction and dermatologic treatment in the management of invasive cutaneous malignant neoplasm: a systematic review of functional and cosmetic outcomes - Arellano Pacheco, Elizabeth; González González, Gilberto; García Rodríguez, Jessica Marissa; Santodomingo Galindo, Andres Felipe; Olivero Díaz, Lina Paola; Jacome Mendoza, Wendy Johana; Franco Osorio, Lucia Margarita; Lazo Jara, Verónica Cristina (Ibero-American Journal of Health Science Research, 2025)
Background: The periocular region is a high-risk site for cutaneous malignancies, particularly basal and squamous cell carcinomas. Because of its role in protecting the eye and supporting tear film dynamics, even small defects in this area can disrupt function and lead to noticeable cosmetic changes. Managing tumors here requires a careful balance between complete cancer removal and preserving eyelid function and appearance. Objective: To evaluate the functional and cosmetic outcomes of combining periocular reconstruction with dermatologic and systemic treatments in patients with invasive periocular skin cancers. Methods: We conducted a systematic review of 57 studies involving patients with invasive cutaneous malignancies of the periocular region. Included treatments spanned Mohs micrographic surgery (MMS), conventional excision with frozen-section control, radiotherapy, and systemic therapies such as vismodegib and cemiplimab. We examined outcomes related to eyelid function, visual protection, tear drainage, and patient-reported cosmetic satisfaction. Results: MMS consistently offered high cure rates and minimal tissue loss, resulting in favorable functional and cosmetic outcomes when paired with oculoplastic reconstruction. Flap techniques such as the Hughes and Mustardé flaps showed high success rates in restoring eyelid structure and function. In advanced cases, neoadjuvant therapies reduced the need for orbital exenteration and preserved visual function in 40–60% of patients. Radiation therapy was effective but often resulted in chronic ocular surface problems. Patients undergoing exenteration reported lower satisfaction despite acceptable prosthetic rehabilitation. Conclusion: A combined approach to periocular skin cancer—integrating precise excision, functional reconstruction, and selective use of systemic therapy—yields better outcomes than single-modality treatment. Multidisciplinary planning is essential to preserve both form and function. Future studies should standardize outcome reporting and include long-term patient-centered data to guide best practices.